The Backwash Effect of the National Exam on Upper Secondary Moroccan Teaching - Riham Belkbir (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
This study aims to investigate the issue of assessment in the Moroccan educational system. Precisely, it aims at exploring the washback of the Secondary national English examination on English teaching and learning practices in the context of upper secondary education in Morocco. To attain the objective of the study, questionnaires are distributed to 70 teachers, and a focus group protocol with 20 students was conducted in three high schools. The findings reveal that the examination has a strong negative influence on the students and the teachers. The main harmful washback effect of this exam is found to be the neglect of teaching the skills of listening and speaking as they are not assessed. Moreover, the results of the study show that the contents of teaching are highly influenced by the exam. Even though the syllabus was changed from grammar-based to communicative-based, English Examinations are still grammar-ruled and reading-based. Similarly, students are also affected by the washback effect of the national exam because it brings anxiety that can distort their progress and performance, and students might not be able to learn real-life knowledge but instead learn discrete points of knowledge that are assessed. On the basis of these results, a new English exam is suggested, hoping to prompt positive washback and refine the English-speaking performance of Moroccan highschoolers.